Does Organic Food Consumption Signal Prosociality? : An Application of Schwartz’s Value Theory - Puska, Petteri (Taylor & Francis, 2018)
Current research suggests that sustainable consumption choices (including favoring organic foods) can act as signals of prosociality. However, who actually perceives such acts as indicators of prosocial, altruistic tendencies is still unclear. Through an online survey (n = 168) and by using personal value priorities (Schwartz’s theory of values) as IVs, the present study sheds light on this issue. First, the results suggest that organic food consumption can confer the valuable signal of prosociality – and some other socially valued traits were also associated with this everyday behavior strategy. Then, the study shows that the interpretation of the signal is dependent on respondents’ positioning in Schwartz’s value circumplex. Intriguingly, in addition to those people who endorse self-transcendence values, people with conservative value priorities also view the presumed organic consumer as prosocial. These impressions are further mediated by more specific organic food attitudes, thereby forming a value–attitude–impression relationship. The implications are outlined.
Keywords: consumer impression; organic food; prosociality; Schwartz’s value theory; status; fi=Markkinointi|en=Marketing|